PERSEPSI PUBLIK TERHADAP PENGGUNAAN ZAKAT BAGI PEMBIAYAAN INFRASTRUKTUR TRANSPORTASI - Mursalim Muddin; Sakti Adji Adisasimita; Rusdi Usman Latief; Suharman Hamzah; Wimpy Santosa (Himpunan Pengembangan Jalan Indonesia (HPJI), 2019)
Abstract Funding needs for infrastructure financing launched by the Government require alternative funding sources. One of the funding sources is community zakat or alms funds. This research is intended to obtain public perception about the use of zakat funds to finance land transportation infrastructure, namely toll roads. This study uses a questionnaire that was filled by respondents who have been selected. The results showed that in general respondents agreed with the use of zakat funds for infrastructure financing, with the proportion of male respondents agreeing more than the proportion of female respondents. A rather different result is obtained if the respondent is asked for his opinion about financing infrastructure investment by the National Zakat Agency in collaboration with a business entity (private) as a contractor or operator. The majority of respondents disagree if zakat funds are used with this scheme, with more female respondents disagreeing. As for short-term infrastructure financing, the majority of respondents, or as many as 59.52% of respondents, agreed that zakat funds are used to finance short-term infrastructure. The proportion of respondents, both men and women, who agree on this scheme is greater than the proportion that does not agree, and is not influenced by their level of education. Keywords: zakat, financing infrastructure, transportation infrastructure, toll roads Abstrak Kebutuhan dana untuk pembiayaan infrastruktur yang dicanangkan oleh pemerintah membutuhkan sumber-sumber pembiayaan alternatif. Salah satu sumber pendanaan tersebut adalah dana zakat masyarakat. Penelitian ini dimaksudkan untuk memperoleh persepsi publik tentang penggunaan dana zakat untuk pembiayaan infrastruktur transportasi darat, yaitu jalan tol. Penelitian ini menggunakan kuesioner yang diisi oleh responden yang telah dipilih. Hasil penelitian menunjukkan bahwa pada umumnya responden setuju dengan penggunaan dana zakat untuk pembiayaan infrastruktur, dengan proporsi responden pria yang setuju lebih banyak daripada proporsi responden wanita. Hasil yang agak berbeda diperoleh bila responden diminta pendapatnya tentang pembiayaan investasi infrastruktur oleh Badan Amil Zakat Nasional bekerjasama dengan badan usaha (swasta) sebagai kontraktor atau operator. Mayoritas responden menyatakan tidak setuju bila dana zakat digunakan dengan skema ini, dengan responden wanita lebih banyak yang tidak setuju. Sedangkan untuk pembiayaan infrastruktur jangka pendek, mayoritas responden, atau sebanyak 59,52% responden, menyatakan setuju bila dana zakat digunakan untuk pembiayaan infrastruktur jangka pendek. Proporsi responden, baik pria maupun wanita, yang setuju pada skema ini lebih besar daripada proporsi yang tidak setuju, dan tidak dipengaruhi oleh tingkat pendidikan mereka. Kata-kata kunci: zakat, pembiayaan infrastruktur, infrastruktur transportasi, jalan tol